Short and Long-Term Effects on Academic Performance of a School-Based Training in Self-Regulation Learning: A Three-Level Experimental Study - Tuero, Ellián; Núñez, José Carlos; Vallejo, Guillermo; Fernández, María Paula; Añón, Francisco Javier; Moreira, Tânia; Martins, Joana; Rosário, Pedro (Frontiers in Psychology, 2022)
An experimental study was designed to analyze the effect of school-based training in self-regulation learning strategies on academic performance (Mathematics, Sciences, Language, English). Class-level variables (i.e., gender, the teacher’s teaching experience, class size) were considered and the effects of the intervention were measured at the end of the intervention and three months later. A sample of 761 students from 3rd and 4th grades (356 in the control condition and 405 in the experimental condition), from 14 schools, participated in the study. Data were analyzed using three-level analysis with within-student measurements at level 1, between-students within-classes at level 2, and between-classes at level 3. Data showed a positive effect of the intervention on student performance, both at post-test (d = 0.25) and at follow-up (d = 0.33) considering the four school subjects together. However, the effect was significant just at follow-up when subjects were considered separately. Student performance was significantly related to the students’ variables (i.e., gender, level of reading comprehension) and the context (teacher gender and class size). Finally, students’ gender and level of reading comprehension, as well as the teacher’s gender, were found to moderate the effect of the intervention on students’ academic performance. Two conclusions were highlighted: first, data emphasize the importance of considering time while conducting intervention studies. Second, more teaching experience does not necessarily translate into improvements in the quality of students’ instruction.